Experience in setting up the tropical forest conservation fund in the Philippines: A civil society perspective - Montemayor, Jerome L. (Animo Repository, 2003)
The paper is about the rich experience and continuing effort of the Core Group on the Tropical Forest Conservation Act (TFCA) Philippines in engaging the United States Government and the Philippine Government towards the establishment of the tropical forest fund. This is the story of how a core group of environment non-government organizations (NGOs) came together to look into the potentials of the debt treatment under the TFCA as an innovative mechanism to financially support protected areas (PAs), in particular, tropical forest. It gives an account of how the Core Group facilitated the regional and national gatherings of representatives of civil society: NGOs, peoples organizations, academicians, funding institutions, and other stakeholders to ensure broad and active participation in the process of shaping the governance of the fund and the possible geographic and thematic priorities. The paper recounts how funders can collaborate to co-finance the activities and processes that would eventually lead to the birth of a new funding in the Philippines: the Tropical Forest Conservation Fund. The author hopes that Southeast Asian countries, which may be eligible to engage in the TFCA, could gain knowledge of the experience and lessons learned in the Philippine experience. Should the civil society in these countries decide to engage in a similar undertaking, this narration of the Philippine experience may serve as a springboard.